Analisis Penggunaan Model Cooperative Integrated Reading and Composition (CIRC) Dalam Meningkatkan Hasil Belajar Siswa di Kelas Tinggi Sekolah Dasar - Siti Hasny Nur; Ahmad Suriansyah; Wahdah Refia Rafianti (STIKes Ibnu Sina Ajibarang, 2025)
This article analyzes the use of the Cooperative Integrated Reading and Composition (CIRC) model in improving student learning outcomes in higher classes. CIRC is a cooperative learning model that integrates reading and writing activities with the aim of improving students’ academic skills. Through a literature review, this article reviews various research related to the implementation of CIRC, as well as its impact on improving learning outcomes, especially in aspects of reading comprehension and writing skills in higher grades. The results of the analysis show that the CIRC model can encourage positive social interactions between students, increase learning motivation, and facilitate the achievement of better learning outcomes. The application of this model has also proven effective in improving students’ cognitive and affective abilities, as well as strengthening understanding of concepts through collaborative learning. This article concludes that CIRC is a potential model to be applied in higher class learning to achieve more optimal learning outcomes.